Staff Note for the G-20-A Guiding Framework for Structural Reforms. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2016)
This note responds to a request from the G20 for IMF assistance in helping develop priorities and guiding principles for structural reforms. Structural reforms have long been a central element of the G20's strategy of achieving job-rich growth, and G20 countries have made over 1,000 structural policy commitments in their national growth strategies. However, implementation of these commitments has been relatively weak so far. Faster progress on structural reforms is therefore needed to support growth in the near term and bolster potential growth in the medium term-and more generally to make economies more innovative, flexible, and resilient.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet